Means-tested transit subsidies in Latin America - Andrés Gómez-Lobo; Santiago Sánchez González; Vileydy González Mejia (Inter-American Development Bank (IDB), 2022)
This paper reviews three targeted transit subsidies applied in Latin America. First, we present the experience of Bogota and Buenos Aires, where demand side means-tested subsidies were introduced during the last decade. In these two cases, criteria from the general welfare system are used to determine eligibility and both have been implemented using smartcard payment technology. We review the available information on the design, operation, and distributional outcomes for each case. This review provides useful information for policymakers interested in the design and implementation of targeted transit subsidies. The third experienced is Brazil's Vale Transporte scheme introduced in 1985. Although widely cited, the distributive impact and potential behavioral changes induced by this subsidy have not been presented in the literature. In this paper we use household survey data for 26 metropolitan areas of Brazil to estimate the distributional impact of the Vale Transporte scheme. The results indicate that this program is badly targeted to low-income individuals. In 19 of the 26 cities, this subsidy is regressive. The reason is that only formal sector workers are eligible for this benefit while many low-income individuals work in the informal sector in Brazil. In addition, since this subsidy is paid by employers it is reasonable to expect compensating equilibrium effects in wages or unemployment. We present evidence that suggests that this may have occurred with wages.
Keywords: 330